Evaluation of the Visual Analog Score (VAS) to Assess Acute Mountain Sickness (AMS) in a Hypobaric Chamber - Wu, Jialin; Chen, Yu; Luo, Yongjun (PLOS ONE, 2014)
Objective The visual analog score (VAS) is widely used in clinical medicine to evaluate the severity of subjective symptoms. There is substantial literature on the application of the VAS in medicine, especially in measuring pain, nausea, fatigue, and sleep quality. Hypobaric chambers are utilized to test and exercise the anaerobic endurance of athletes. To this end, we evaluated the degree of AMS using the visual analog scale (VAS) in a hypobaric chamber in which the equivalent altitude was increased from 300 to 3500 m. Methods We observed 32 healthy young men in the hypobaric chamber (Guizhou, China) and increased the altitude from 300 to 3500 m. During the five hours of testing, we measured the resting blood oxygen saturation (SaO2) and heart rate (HR). Using the VAS, we recorded the subjects' ratings of their AMS symptom intensity that occurred throughout the phase of increasing altitude at 300 m, 1500 m, 2000 m, 2500 m, 3000 m, and 3500 m. Results During the phase of increasing altitude in the hypobaric chamber, the patients' SaO2 was 96.8±0.8% at 300 m and 87.5±4.1% at 3500 m (P<0.05) and their HR was 79.0±8.0 beats/minute at 300 m and 79.3±11.3 beats/minute at 3500 m. The incidence of symptoms significantly increased from 21.9% at an altitude of 1000 m to 65.6% at an altitude of 3500 m (P<0.05). The composite VAS score, which rated the occurrence of four symptoms (headache, dizziness, fatigue, and gastrointestinal discomfort), was significantly correlated with elevation (P<0.01). Conclusion Based on the experimental data, the VAS can be used as an auxiliary diagnostic method of Lake Louise score to evaluate AMS and can show the changing severity of symptoms during the process of increased elevation in a hypobaric chamber; it also reflects a significant correlation with altitude.